Direct hydrodeoxygenation of algal lipids extracted from Chlorella alga. Issue 4 (23rd January 2017) - Nguyen, Hoang SH; Mäki‐Arvela, Päivi; Akhmetzyanova, Uliana; Tišler, Zdeněk; Hachemi, Imane; Rudnäs, Andre; Smeds, Annika; Eränen, Kari; Aho, Atte; Kumar, Narendra; Hemming, Jarl; Peurla, Markus; et al.
Abstract: BACKGROUND: Hydrodeoxygenation (HDO) of Chlorella algal oil extracted with supercritical hexane and stearic acid as a model compound was investigated over several supported Ni and Mo2 N–MoO2 catalysts in a semibatch reactor at 300 °C under 30 bar in the presence of hydrogen. RESULTS: The results showed that all catalysts were very active in HDO of stearic acid. With crude algal oil, a maximum conversion of lipids of 35% was found with an acidic Ni‐HY‐80 zeolite catalyst after 360 min. The main products in algal oil HDO were fatty acids; whereas maximally only 7% hydrocarbons were formed with Ni‐HY‐80. The main hydrocarbon products were formed via decarbonylation, as the hydrogenation/dehydration route was suppressed. CONCLUSIONS: Hydrodeoxygenation of crude Chlorella algal oil was demonstrated over nickel supported on beta zeolite and with a molybdenum oxide–nitride catalyst. Strong catalyst deactivation occurred for the former catalyst, whereas the latter retained its activity. © 2016 Society of Chemical Industry